Glacigenic postglacial faulting at Saint John, New Brunswick - Broster, B.; Burke, K. (Atlantic Geology, 1990)
Displaced glacial striae were examined at outcrops within the central area of Saint John, New Brunswick. Displacements are mostly confined to north-facing slopes of small bedrock hills left after the glacial erosion of Cambrian-Early Ordovician rocks in the southeast limb of a syncline. The striae are generally offset by high-angle reverse faults a few metres in length and with throws up to 60 mm. The faults trend parallel to bedding and dip southward at angles similar to the dip of individual beds. The displacements have long been considered as evidence of postglacial tectonic stresses in the area. However, from a detailed analysis of the extent and orientation of the small faults, we propose that the displacements represent the response of multilayered sedimentary rocks with anisotropic strengths, to differential rates of glacitec tonic loading and unloading. Therefore, the last major displacements likely occurred very soon after deglaciation of the area.